Evaluating the Role of Atropine Sulphate in Preventing Motion-Related Postoperative Nausea and Vomiting in Patients Undergoing Cesarean Section using ERACS Protocol - Rahmadinie, Amalia; Agastya, Wayan Dhea (Jurnal Kesehatan Islam : Islamic Health Journal, 2025)
ABSTRACT Background: PONV is common after cesarean section using ERACS protocol. Motion-related PONV during early mobilization can impair comfort and delay recovery. Anticholinergic agents such as atropine sulphate have antiemetic effects via muscarinic receptor antagonism, especially when vestibular pathways are involved, but their intravenous use for motion-related PONV prevention remains underexplored. Objective: To evaluate the effectiveness of intravenous atropine sulphate in reducing motion-related PONV within two hours postoperatively in patients undergoing cesarean section. Methods: A retrospective cross-sectional analysis was carried out involving 30 patients at a private hospital in Sidoarjo, Indonesia (May–June 2025). Patients were assigned to either control (no atropine) or treatment (0.5 mg atropine IV after cord clamping). The primary outcome was a combined PONV score: (1) vomiting episodes ≥ 1, (2) moderate-to-severe nausea/vomiting (VAS > 4), and (3) rescue antiemetic use. Secondary outcomes included atropine-related adverse effects. Results: The treatment group had significantly lower mean combined PONV scores (p < 0.001), fewer vomiting episodes (p = 0.035), less moderate-to-severe nausea (p = 0.002), and borderline reduced rescue antiemetic use (p = 0.05). No significant adverse effects were observed. Conclusion: IV atropine sulphate 0.5 mg after cord clamping effectively reduces motion-related PONV in ERACS cesarean patients without notable side effects. Keywords: atropine sulphate, cesarean section, ERACS, PONV vestibular pathway.